Citra Perempuan dalam Novel Burung-Burung Manyar Karya YB Mangunwijaya: Kajian Analisis Isi - Zainun Nasichah (Universitas Muhammadiyah Prof. DR. HAMKA, 2016)
This reseach aims to identify and analyze the image of women contained in the novel The Birds Manyar works Mangunwijaya YB (Content Analysis Studies). The method used in this research is a qualitative descriptive method by content analysis. The object of this research is the novel The Birds Manyar YB work. Mangunwijaya. the focus of this study is the image of women contained in the novel The Birds Manyar YB work. Mangunwijaya. The instrument of this study is the researchers themselves assisted with analysis tables. data analysis conducted by researchers of reading the novel The Birds Manyar YB work. Mangunwijaya, analyzing aspects of the image of women, include the results of the analysis and concludes the analysis results. The image of women analyzed in this study are include (1) the image of women physically, (2) the image of women psychologically, (3) the image of women's role in the family, (4) the image of women's role in society. The results obtained from the analysis of data on novel birds Manyar YB work. Mangunwijaya said the image of women are physically the most prominent is the image of women that beautiful face, whereas the image of women psychologically is the most dominant image of the psyche of women as a human being who is passionate, he is spontaneous and impulsive, whereas the image of women's role in the family's most prominent is the image of women as mothers and educators of their children, and the image of women's role in society is the most prominent image of women who dare to fight for the principles and aspirations. This research has implications for literary appreciation learning in high schools, in particular on the intrinsic elements of the female characters in the novel, to increase knowledge and improve the ability of students to the literary appreciation of literature, especially the novel The Birds Manyar YB Mangunwijaya work It is concluded that the image of women that look the most dominant in Novel birds Manyar YB Mangunwijaya work is psychologically female image of women as a human being who is passionate , he is spontaneous and impulsive .